Development of interactive multimedia on social studies learning outcomes of elementary school students - Suryana Rajagukguk; Samsidar Tanjung; Restu Restu (Inovasi Kurikulum, 2025)
The lack of interesting interactive learning media causes the low learning outcomes of social studies in primary schools. Monotonous learning methods make students less motivated and involved in the learning process. This study aims to develop and analyze the effectiveness of interactive multimedia based on Articulate Storyline 3 in improving learning outcomes. The method used is Research and development (RnD) with the 4-D development model (Define, Design, develop, disseminate). The research subjects were 25 students of class IV UPT SDN 064992. Data were collected through observation, interviews, expert validation questionnaires, and effectiveness tests using the N-gain method. The results showed that using Articulate Storyline 3 improved student learning outcomes with an N-gain of 0.39. Evaluations from teachers and students also show that this media is suitable for learning, but it still needs appearance and navigation improvement. In conclusion, Articulate Storyline 3 effectively improves social studies learning outcomes. Future research is recommended to develop adaptive features and gamification to increase student engagement in the learning process in the classroom.   Abstrak Rendahnya hasil belajar IPS di sekolah dasar disebabkan oleh kurangnya media pembelajaran interaktif yang menarik. Metode pembelajaran yang monoton membuat peserta didik kurang termotivasi dan terlibat dalam proses belajar. Penelitian ini bertujuan untuk mengembangkan dan menganalisis efektivitas multimedia interaktif berbasis Articulate Storyline 3 dalam meningkatkan hasil belajar. Metode yang digunakan adalah Research and Development (RnD) dengan model pengembangan 4-D (Define, Design, Develop, Disseminate). Subjek penelitian adalah 25 peserta didik kelas IV UPT SDN 064992. Data dikumpulkan melalui observasi, wawancara, angket validasi ahli, dan uji efektivitas menggunakan metode N-gain. Hasil penelitian menunjukkan bawah penggunaan Articulate Storyline 3 meningkatkan hasil belajar peserta didik dengan N-gain sebesar 0.39. Evaluasi dari guru dan peserta didik juga menunjukkan bahwa media ini layak digunakan dalam pembelajaran, meskipun masih perlu perbaikan pada tampilan dan navigasi. Kesimpulannya, Articulate Storyline 3 efektif dalam meningkatkan hasil belajar IPS. Penelitian selanjutnya disarankan untuk mengembangkan fitur adaptif dan gamifikasi guna meningkatkan keterlibatan peserta didik dalam proses pembelajaran di kelas. Kata Kunci: articulate storyline; IPS; media interaktif; sekolah dasar